Adoption of onfarm hermetic storage for cowpea in West and Central Africa in 2012 - Moussa, B.; Abdoulaye, Tahirou; Coulibaly, O.; Baributsa, D.; Lowenberg-Deboer, J. (Elsevier, 2014)
This study is based on interviews with 3456 randomly selected cowpea farmers in 322 villages in ten countries in West and Central Africa in 2010 and 2012. It uses descriptive statistics to track the trends in adoption of cowpea storage technology compared to previous studies and Firth logistic regression to identify important factors in adoption. The interviews indicate that regionally about 46% of respondents use some type of hermetic storage for their cowpeas and about 44% of the quantity of cowpea stored on farms is in hermetic containers. Both the percentage of respondents and the percentage of stored quantity fall slightly short of the 50% benchmark hypothesized. The 2010e2012 estimates compare to about 30% of cowpea quantity stored in hermetic containers in 2003e2004. Regionally, the most commonly used hermetic storage container is the triple layer Purdue Improved Cowpea Storage (PICS) bag. In PICS villages, local unavailability is the most common reason for not using the bags. The logit analysis shows that living in a village with PICS activities is the single most important factor explaining adoption of the technology. In six of the nine regressions participation in the demonstrations was also positive and a statistically significant determinant of adoption. For someone living in a PICS village and participating in the activities the combined effect is highly influential. In Niger such an individual would be 27% more likely than a non-participant from a non-PICS village to use PICS bags. In Senegal he or she would be 55% more likely. Some form of exposure to PICS activities or village technicians is key in adoption of the PICS technologies, though it may not be direct contact with a PICS technician. On average additional cash flow due to storage of cowpea in PICS bags is estimated at $26.58/100 kg bag more than sale at harvest.